Investigations of plants of the genus Heracleum autochthonous for Southeastern Europe - searching for new natural medicinal raw materials - Ušjak, Ljuboš (Archives of Pharmacy, 2022)
Significance of pharmacognostic studies on previously untested or scarcely tested wild plants is constantly rising, considering growing demand of pharmaceutical industry for new bioactive isolates, including essential oils and extracts. Accordingly, comprehensive research that included all nine taxa of genus Heracleum L. (Apiaceae) (three of which are endemic) from Serbia, Montenegro, North Macedonia and Slovenia was performed (60 samples of various plant organs collected from 14 localities in period 2009-2016). Plants of this genus (cow parsnips) got their Latin name after ancient hero Heracles, because of their habitus and use in folk medicine in treatment of various diseases. Also, some of them were the main ingredient of borscht, a traditional dish in Eastern European countries. They are interesting because of wide range of metabolites: from essential oil components, coumarins, flavonoids, phenolic acids, triterpenes and phytosterols, to some specific fatty acids. Analysis of these secondary and primary metabolites was performed using modern chromatographic and spectroscopic techniques (GC-FID-MS, LC-MS and NMR). In the case of 35 selected essential oils, antimicrobial, cytotoxic and/or antioxidant activities were also tested. It was revealed that studied plants represent potential new sources of compounds of importance not only for pharmaceutical, but also for cosmetic, food and chemical industries. For components of essential oils and furanocoumarins, by multivariate statistical analysis, chemosystematic significance was also established. Results of pharmacological investigations of essential oils indicated their importance as potential new medicinal plant raw materials, under condition of respecting established maximum daily intakes for those oils in which furanocoumarins were detected.